In cellulo structure determination of a novel cypovirus polyhedrin. (1st May 2014) - Axford, Danny; Ji, Xiaoyun; Stuart, David I.; Sutton, Geoff
<x xml:space="preserve">Abstract</x> This work demonstrates that with the use of a microfocus synchrotron beam the structure of a novel viral polyhedrin could be successfully determined from microcrystals within cells, removing the preparatory step of sample isolation and maintaining a favourable biological environment. The data obtained are of high quality, comparable to that obtained from isolated crystals, and enabled a facile structure determination. A small but significant difference is observed between the unit‐cell parameters and the mosaic spread of in cellulo and isolated crystals, suggesting that even these robust crystals are adversely affected by removal from the cell.